Methodology For Developing Professional Skills In Students Based On International Assessment Programs - Alibek Bolatbekovich Kaldibekov (Euro Asian Journal Publishing, 2024)
This article shows interactive methods, application and design methods of innovative technologies in technological education classes.
Keywords: student; profession; skill; international